Design and construction of attire dryer for high-rise building - Lam, Chin Yueh (University Malaysia Sarawak, UNIMAS., 2004)
A solar attire dryer was designed, constructed and tested. In this project, several technical performance tests have been conducted to study the application of the greenhouse effect solar dryer systems.